Intermediate-Term Variations İn Solar Radius During Solar Cycle 23 - Gölbaşı, Orhan; Kılıç, H.; Chollet, F. (Wiley-V C H Verlag Gmbh, Po Box 10 11 61, D-69451 Weinheim, Germany, 2009)
In this study, we look for the mid-term variations in the daily average data of solar radius measurements made at the Solar Astrolabe Station of TUBITAK National Observatory (TUG) during solar cycle 23 for a time interval from 2000 February 26 to 2006 November 15. Due to the weather conditions and seasonal effect dependent on the latitude, the data series has the temporal gaps. For spectral analysis of the data series, thus, we use the Date Compensated Discrete Fourier Transform (DCDFT) and the CLEANest algorithm, which are powerful methods for irregularly spaced data. The CLEANest spectra of the solar radius data exhibit several significant mid-term periodicities at 393.2, 338.9, 206.5, 195.2, 172.3 and 125.4 days which are consistent with periods detected in several solar time series by several authors during different solar cycles. The knowledge relating to the origin of solar radius variations is not yet present. To see whether these variations will repeat in next cycles and to understand how the amplitudes of such variations change with different phases of the solar cycles, we need more systematic efforts and the long-term homogeneous data. Since most of the periodicities detected in the present study are frequently seen in solar activity indicators, it is thought that the physical mechanisms driving the periodicities of solar activity may also be effective in solar radius variations. (C) 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: Sun: activity; Sun: fundamental parameters; Sun: general; Sun: oscillations; calern-observatory astrolabe; diameter measurements; ccd astrolabe; flare occurrence; spectral-analysis; periodicities; sun; solar-cycle-23; period; index; Güneş: etkinlik; Güneş: Temel parametreler; Güneş: Genel; Güneş: salınımlar; çap ölçümleri; spektral analiz; Güneş döngüsü-23; indeks